Amplification of specific chromosomal regions assessed by fluorescent in situ hybridization on Pap smears to be added as screening tool for identifying women at risk of progressing to cervical cancer - Pavani Upendram; Shubhi Sahni; Khaliq Mohiuddin; Subhadra Poornima; Bhanumathy Gourishankar; Kiran Kumar Vattam; Pavani Boddala; E Jayashankar; Shakera Mohiuddin; Vasundhara Kamineni; Vasavi Mohan; Jane Houldsworth; et al. (Tumor Biology, 2017)
Cervical carcinoma is a frequent malignancy in developing countries despite being a preventable disease. For the first time, four screening tests were used simultaneously for identifying women with a risk of developing cervical cancer, to help clinicians and policy makers to implement the best strategy for reducing the burden of this disease. Women visiting a hospital in India were enrolled after institutional ethics clearance and informed consent. Visual inspection using acetic acid and Pap smear tests were performed on 2683 women, and 104 had abnormal cytology: atypical squamous cells of undetermined significance (n = 29), low-grade squamous intraepithelial lesion (n = 41), high-grade squamous intraepithelial lesion (n = 17), and squamous cell carcinoma (n = 17). These and 96 samples, with normal cytology, were subjected to high-risk human papilloma virus testing and fluorescent in situ hybridization evaluation. Women with abnormal cytology were followed for 5 years and evaluated with colposcopy-guided biopsy. Three accepted methods of screening and one novel fluorescent in situ hybridization assay were carried out in 200 cases. Cutoffs for fluorescent in situ hybridization were established. The screening methods had 88%–96% negative predictive value, while positive predictive value was low (20%) for visual inspection using acetic acid, 47% for fluorescent in situ hybridization, 56% for high-risk human papilloma virus, and 73% for combined high-risk human papilloma virus and fluorescent in situ hybridization. Combined high-risk human papilloma virus and fluorescent in situ hybridization had 94% sensitivity, specificity, and negative predictive value, suggesting that simultaneous screening with these two tests is appropriate for identifying women progressing to cervical cancer and not visual inspection using acetic acid, which has low positive predictive value and Pap cytology which requires to be repeated. Policy makers and clinicians can assess feasibility of incorporating this screening strategy to prevent cervical cancer.